Somatic embryogenesis in holm oak male catkins - Blasco, M.; Barra, A.; Brisa, C.; Corredoira, E.; Segura, J.; Toribio, M.; Arrillaga, I. (Plant Growth Regulation, 2013)
Somatic embryogenesis (SE) of tree species is the most promising method for the implementation of multivarietal forestry and for biotechnological approaches. To date, however, the application of this technology to mature trees is restricted to a few species. This is the first report on the induction of SE from male catkins of 100-year-old holm oaks (Quercus ilex L.). Embryogenic competence was mainly dependent on genotype and restricted to the most advanced catkin developmental stage with distinguishable closed flowers along the axis. Fol- lowing a three-stage treatment procedure, embryogenic response (frequencies up 3.3 %) was obtained in three [Remedio, Villar del Arzobispo (VA) and Hunde (HU)] out of the five genotypes evaluated. In the culture conditions tested, the preferred protocol to induce SE in holm oak catkins should include: induction on MS medium with 6-benzyladenine and naphthaleneacetic acid, subculture onto medium with a reduced concentration of both plant growth regulators and a final transference to medium without growth regulators. Under these conditions cotyledonary-stage cotyledonary-stage somatic embryos developed from brown calli with or without nodular structures. Secondary SE, favored by the addition of sorbitol to the manifestation medium, allowed the establishment of 14 embryogenic lines belonging to VA and HU genotypes. Histological observations of the proliferating cultures revealed the presence of globular, torpedo and cotyledonary somatic embryos. Somatic embryos were diploid as verified by flow cytometry analysis, suggesting that they originated from the perianthic tissue of the male flower
Keywords: adult trees; developmental stage; flow cytometry; forest biotechnology; histology; micropropagation; Quercus ilex; secondary embryogenesis

PRODUCCIÓN DE PLANTA CLONAL DE QUERcus ILEX L. MEDIANTE EMBRIOGÉNESIS SOMÁTICA PARA MICORRIZACIÓN CON TUBER MELANOSPORUM Vitt. - Mauri, P V; Garcia, G; Fernandez-Galiano, E (II Congreso Forestal Español, 1997)
Quercus ilex L. is the most important tree for the micorritation with Tuber melanosporum Vitt. Quercus ilex L. acorns were collected during the summer and they were surface sterilized with a 15% NaC10H solution. Zygotic embryos were then plated in darlrness during 30 days in a MS medium containing PRL-4-C macrosalts. Different concentrations of growth regulators (NAA, BA and 2,4D) were added to the basic medium for inducting somatic embryogenesis. Explants were transferred to a basal medium supplemented with 0,5 MBA and 0,5 MNAA, during 30 days in light. The somatic embryogenesis response appeared in every media assayed, even in the one with no PGRs, except in those containing 3. M 2,4D. The somatic embryos appeared from embryogenic yellow, friable callus or directly from the apical axis. Once the embryonic callus was transferred to PGRs free medium, secondary embryogenesis appeared repetitively. Somatic embryogenesis in Quercus ilex L. seems not to dependent on the PGRs added, appearing even with no PGRs. Secondary embryogenesis allows a continuing production of somatic embryos, essential to obtain high amounts of clonal plants.
Keywords: Plant Growth Regulators; Quercus ilex L.; secondary embryogenesis; Somatic embryogenesis; Tuber melanosporum Vitt.; zygotic embryos

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B.; Celestino, C.; Toribio, M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B; CELESTINO, C; TORIBIO, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis

Histology of Callogenesis and Somatic Embryogenesis Induced in Stem Fragments of Cork Oak (Quercus suber) Cultured In Vitro - MAÂTAOUI, M E L; Espagnac, H; MICHAUX-FERRIÈRE, N (Annals of Botany, 1990)
Calluses able to produce somatic embryos were formed during in vitro culture of shoot fragments of cork oak (Quercus suber L.).Histological monitoring of these fragments during culture showed that it was the cortical parenchyma cells which underwent dedifferentiation before calluses were formed by repeated divisions. The calluses consisted of parenchyma cells surrounded by a few layers of meristematic cells. Proembryos formed in groups around the edge of some calluses. Histological examination showed that they were produced by the evolution of two different categories of cell: one category had the appearance of ‘embryogenic’ cells with very thick walls, a small vacuole rich in starch and a well-developed nucleus with a prominent nucleolus. The other cells were very bulky with large vacuoles; their morphology was similar to that of suspensor cells encountered in embryogenesis in gymnosperms. The ontogenic stages were similar to those described in zygotic embryos of the genus Quercus. Nevertheless, most of the embryonic structures deviated from normal development and at all stages produced secondary proembryos.
Keywords: callogenesis; cork-oak; embryogenic cells; histology; Quercus suber L.; secondary embryogenesis; Somatic embryogenesis; starch